Depopulation and availability of services, contents for social participation and infrastructure in rural settlements – illustrated by the devastated municipalities in South-Eastern Serbia - Jelić, Sreten; Kolarević, Vukašin Ž. (Sociološki pregled, 2022)
Depopulation of rural areas as a global process has not bypassed our country either. Demographic changes in the structure of the population have especially affected the rural population and the village in our society. Depopulation of a number of villages, especially in South-eastern Serbia, means that some villages are almost empty or with older people and a minor share of young people. The aim of this paper is to analyze the availability of services, social participation contents and the quality of infrastructure in rural settlements. Therefore, the research was conducted on the basis of a survey questionnaire in 176 rural settlements in the municipalities of Bojnik, Crna Trava, Medveđa, Surdulica and Trgovište. The findings indicate the extent to which negative indicators of the number of inhabitants in rural settlements are related to available services, social participation contents and infrastructure based on the correlation analysis.
Keywords: depopulation; availability of services; infrastructure; social participation contents; rural settlements